Studi Eksistensi Etnis Rohingya di Tengah Tekanan Pemerintah Myanmar - Anna Yulia Hartati (Jurnal Hubungan Internasional, 2013)
This article is trying to explain the roots of ethnic conflict in Myanmar, and what are the implications of the conflict. Ethnic conflict involves two ethnic groups are ethnic Rohingya Muslim and ethnic Buddha Rakhine. This conflict causes thousands of people trying to escape every year to Bangladesh, Malaysia and other places in the area. People try to escape because their rights are not given by the government Myanmar. The causes of ethnic conflict can be seen from three levels, which are Systemic level, which stated that the government’s Myanmar had conspired with foreign investors, Domestic level who said that the government Myanmar led by a military junta, and perception level that stated if ethnic Rohingya is similar to the Benggali. This conflict leads to refugees on the large scale and humanitarian issues and invite the reaction of the international community and the UN.